Enhancing Mobile Interaction for Individuals With Tremors via Optical See-Through Augmented Reality - Zhi Sun; Ruiqing Zhou; Kai Wang; Zhe Li (IEEE Access, 2024)
Mobile phones are central to modern communication, yet for individuals with tremors, the precision required for touch-based interfaces is a significant hurdle. In pursuit of social equality and to empower those with tremors to interact more effectively with mobile technology, this study introduces an optical see-through Augmented Reality (AR) system equipped with a stabilized filter. This system is specially designed to assist individuals with tremors by stabilizing and translating shaky movements into precise virtual commands, allowing users with hand tremor to perform interactions with mobile more effectively and accurately. The first experiment assessed the stabilized filter’s effectiveness using a one-way Analysis of Variance (ANOVA), comparing task completion times with and without the filter. The results showed a statistically significant improvement in operation times with the filter. Subjective evaluations from participants further corroborated these findings, with users reporting a notably better interaction experience when the filter was applied. Feedback highlighted the filter’s stabilization capabilities and its facilitation of smoother interactions, leading to increased user satisfaction and comfort. The second phase of our research involved a comparative analysis, investigating the interactions of individuals with and without simulated tremors using two distinct interfaces within various environments. The experiment was structured around a matrix of conditions comprising two system types (Mobile and AR), two interface designs (Traditional and our Redesigned Interface), and two user states (Non-simulated and Tremor-simulated). Performance metrics focused on task completion times and user feedback via questionnaires revealed that the AR environment was deemed more conducive to operation by those with simulated tremors, due to improved accessibility and interaction quality. In conclusion, this research confirms that the AR system with the stabilized filter represents a meaningful advancement in assistive technologies for tremor patients. The positive response from the tremor community signals the AR system’s promise in fostering greater technological inclusivity and independence for individuals with motor impairment.